Strategi Green Economy Dalam Meningkatkan Ketahanan Keuangan Sektor Migas - Dita Fitriani; Indri Widya Wulandari; Reza Mutiara Nur Fitriandinni; Maria Yovita R Pandin (CV. Ulil Albab Corp, 2024)
This study aims to analyze the effect of green economy strategy on financial resilience at PT Pertamina. Green economy is an economic concept that aims to improve social welfare and community justice by reducing negative impacts on the environment. Green economy strategies include energy efficiency, emission reduction, and waste management, which are expected to improve the company's financial resilience. The research method used is quantitative with data analysis using SmartPLS-4 on a sample of 3 Pertamina subsidiaries listed on the Indonesia Stock Exchange for the period 2020-2022. The results showed that the green economy strategy with indicators of emission reduction and waste management has a positive and significant effect on financial resilience with ROA and profit margin indicators. Thus, the implementation of a green economy strategy can improve the company's financial resilience through reduced costs, increased revenue, and risk mitigation. This research suggests companies to implement green economy strategies as an integral part of the company's operations to improve financial resilience in the long term.